The Three Sons of Noah Civilization Spread - Abdul Haq, Moh Mansur; Abdul Gofar, Muhamad Mushollih; Hidayat, Mukhammad Syariful (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
Taufan of Nuh caused the entire surface of the earth to be destroyed, except for Nuh’s three sons, their wives and Nuh. The Qur'an only informs us that the descendants of Nuh continued his lineage but does not explain the spread of their civilizations. This article aims to discuss the civilization spread of Nuh’s three sons to three continents and their dominance in the central region (Arab). Using qualitative methods (library research) with a descriptive-analysis approach. Data sources were obtained through observations in divine books, especially the Al-Qur’an, tafsir books and books and journals that fit the theme. From the data that has been collected, it was found that all the nations in the world, namely on the first three continents (Africa, Asia and Europe) came from the descendants of Nuh, namely Sam, Ham and Yafits. Yafits has 7 children, most of whose descendants inhabited the European continent. Ham has 4 children, his descendants inhabited the African continent. Meanwhile, Sam has 5 children, among whom were the prophets and messengers such as Ismail, Ishaq and the Prophet Muhammad, as well as great nations, including the Arabs, who created extraordinary civilization, science and art.